Low temperature structural anomalies arising from competing exchange interactions in pyrochlore Nd2Ru2O7 probed by XRD and EXAFS1. Issue 36 (28th September 2015) - Chen, Shi-Wei; Fu, Shao-Wei; Pao, Chih-Wen; Lee, Jenn-Min; Chen, Shin-An; Haw, Shu-Chih; Lee, Jyh-Fu; Liu, Chun-Hsia; Chang, Chung-Kai; Chuang, Yu-Chun; Sheu, Hwo-Shuenn; Lu, Kueih-Tzu; et al.
<x xml:space="preserve">Abstract</x> Quantitative structural parameters of pyrochlore Nd2Ru2O7, with temperature dependence, have been derived upon fitting XRD and EXAFS data.